Brexit and Its Aftermath - What now for Britain and EU? - Mordecai, Aédán (2016)
Britain voted to end its long-standing membership with the EU and in doing so started a possibly long period of economic insecurity with global repercussions. Borne from the disillusionment of the working classes, many wonder what will be next for the UK and the EU.